Theoretical resonant electron-impact vibrational excitation, dissociative recombination and dissociative excitation cross sections of ro-vibrationally excited BeH+ ion. (24th February 2017) - Laporta, V; Chakrabarti, K; Celiberto, R; Janev, R K; Mezei, J Zs; Niyonzima, S; Tennyson, J; Schneider, I F
Abstract: A theoretical study of resonant vibrational excitation, dissociative recombination and dissociative excitation processes of the beryllium monohydride cation, BeH +, induced by electron impact, is reported. Full sets of ro-vibrationally-resolved cross sections and of the corresponding Maxwellian rate coefficients are presented for the three processes. Particular emphasis is given to the high-energy behaviour. Potential curves of 2 Σ +, 2 Π and 2 Δ symmetries and the corresponding resonance widths, obtained from R -matrix calculations, provide the input for calculations which use a local complex-potential model for resonant collisions in each of the three symmetries. Rotational motion of nuclei and isotopic effects are also discussed. The relevant results are compared with those obtained using a multichannel quantum defect theory method. Full results are available from the Phys4Entry database.